Balancing between Local Requirements, Interoperability Standards, and SOA principles ‐ Case eBooking of Health Services - Juha Mykkänen; Mika Tuomainen (Finnish Social and Health Informatics Association, 2012)
Service‐oriented architecture is an attractive development approach for flexible and reusable healthcare IT solutions. However, there are many practical architectural challenges in developing Service‐Oriented Architectures (SOA) in organizations. In practice, not all basic SOA principles can be easily followed using vertical standards and local adaptation is typically needed. In this paper, we discuss balancing between vertical interoperability standards, local requirements and SOA principles. We classify different types of conflicts between these elements and analyze healthcare electronic booking solutions as a case example. The establishment of inter‐organizational interoperability solutions requires agreements on many levels, and open vertical standards such as HL7 combined with horizontal industry standards provide solutions to many of these levels. SOA based interfaces using vertical industry standards and models are good starting points, but they must be further refined to guarantee interoperability and fit for local requirements.